Autonomous Learning Capacity of University Students’ during the COVID-19 Pandemic - Vitri Angraini Hardi; Muhammad Syahrul Rizal; Iska Noviardila (AL-ISHLAH: Jurnal Pendidikan, 2022)
The research aimed to describe the students’ autonomous learning capacity during the COVID-19 pandemic. Descriptive quantitative research was conducted with 269 students of Education faculty, the University of Pahlawan as the research sample that was selected through a simple random sampling technique. The questionnaire was used as a research instrument.   The questionnaire with four Likert scales was distributed to the sample with five indicators.  To analyze the data, the researcher used descriptive statistical analysis.  The findings of the research were as follows: 1). The students agreed that they could formulate their own learning objectives. In addition, several learning activities designed are prepared to help them to reach the learning objective. 2). They agreed that they adjusted the study plan by considering personal needs, including the time schedule as detailed as possible. 3). They claimed that they are acknowledged with learning strategy and implement it in the routine learning process intentionally. 4). The students reported that several changes were adapted in terms of learning strategy if it is necessary as well as considering personal capability. 5). They agreed that monitoring and evaluation of the whole learning process are necessary. This study concluded that the integration of technology in the learning process during the COVID-19 pandemic is a positive thing.